The Influence of Transformational Leadership, Job Satisfaction on Organizational Citizenship Behavior Mediated by Employee Engagement at Bank Sumsel Babel - Fallash, Andry; Helmi, Sulaiman; Gujarto, Muji; Mellita , Dina (Formosa Journal of Multidisciplinary Research, 2024)
This article examines the effect of transformational leadership and job satisfaction on Organizational Citizenship Behavior (OCB) with employee engagement as the mediation at Bank Sumsel Babel. This study uses a quantitative approach with data collection through employee surveys. The results of the analysis indicate that transformational leadership and job satisfaction have a significant positive effect on OCB. In addition, employee engagement is proven to mediate the relationship between transformational leadership, job satisfaction, and OCB. These findings underscore the importance of strengthening employee engagement in improving constructive organizational behavior, with implications for human resource management practices in the banking sector.